2016
DOI: 10.1155/2016/2518596
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Forearm Nerve Blocks: A Novel Application for Pain Control in Adult Patients with Digit Injuries

Abstract: Phalanx fractures and interphalangeal joint dislocations commonly present to the emergency department. Although these orthopedic injuries are not complex, the four-point digital block used for anesthesia during the reduction can be painful. Additionally, cases requiring prolonged manipulation or consultation for adequate reduction may require repeat blockade. This case series reports four patients presenting after mechanical injuries resulting in phalanx fracture or interphalangeal joint dislocations. These pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Regional anesthesia has been shown to reduce the utilization of systemic analgesics and their subsequent side effects [1, 2, 5]. Examples of commonly used UGRA in the emergency department include fascia iliaca compartment blocks in patients with hip and proximal femur fractures [1, 2, 5–8], interscalene brachial plexus blocks in patients with shoulder dislocations [9], serratus anterior plane blocks in patients with rib fractures [10], and forearm nerve blocks in patients with hand injuries [1013]. Studies have shown that medical training on simulation models is an effective way to learn new procedures and ultrasound techniques [1416].…”
Section: Introductionmentioning
confidence: 99%
“…Regional anesthesia has been shown to reduce the utilization of systemic analgesics and their subsequent side effects [1, 2, 5]. Examples of commonly used UGRA in the emergency department include fascia iliaca compartment blocks in patients with hip and proximal femur fractures [1, 2, 5–8], interscalene brachial plexus blocks in patients with shoulder dislocations [9], serratus anterior plane blocks in patients with rib fractures [10], and forearm nerve blocks in patients with hand injuries [1013]. Studies have shown that medical training on simulation models is an effective way to learn new procedures and ultrasound techniques [1416].…”
Section: Introductionmentioning
confidence: 99%
“…Studies measuring feasibility have found that these blocks can be done in less than 10 minutes, and without significant complications [ 12 , 17 ]. Recent emergency medicine literature has demonstrated the successful use of US-guided regional nerve blocks in the ED for finger reduction [ 18 ], upper extremity fractures, dislocations, abscess drainage [ 17 ], and hand blast injuries [ 9 ]. Widespread adoption of US-guided nerve blocks can add to a larger portfolio of multimodal analgesia and limit exposure to opioids.…”
Section: Discussionmentioning
confidence: 99%